High Transmissibility During Early HIV Infection Among Men Who Have Sex With Men-San Francisco, California. - Hollingsworth,TD; Pilcher,CD; Hecht,FM; Deeks,SG; Fraser,C (Journal of Infectious Diseases, 2015)
We estimate the relative transmission rate in early versus later infection among men who have sex with men (MSM) in San Francisco, California, by studying the characteristics of a sample of transmitters, recruited through newly diagnosed, recently infected MSM between 1996 and 2009. Of 36 transmitters identified, 9 were determined on the basis of testing history and serologic testing to have been recently infected. The unadjusted odds ratio of transmitting during early infection was 15.2 (95% confidence interval [CI], 6.3-33.4; P < .001); the odds ratio was 8.9 (95% CI, 4.1-19.4) after adjustment for self-reported antiretroviral treatment. This high transmissibility could be due to both high infectiousness and high rates of sex partner change or concurrent partnerships.